Ambivalence terena - Fikfak, Jurij (Opera ethnologica Slovenica, 2014)
This text about the ambivalence of fieldwork, rituals, actors, and stories thematizes the relationship between the researcher and his informants and interlocutors (usually also the performers of a cultural practice), and it reveals dynamic processes at the same time. In the chapter "Texts and Realities" the author uses the carnival tradition known as škoromatija to decode a palimpsest structure and syncretic understanding of reality. The second chapter focuses on the production of local identity: a motif that is characteristic for today's production of ritual practices and cultural heritage. The chapter "Illusions of Harmony" thematizes discourse on the relationship between the views and conceptions of the researcher and performer, whereby the author especially problematizes the search for and repeated discovery of golden eras. "The Timing of Verbalization" is a narrative about time as one of the most important categories of structuring a narrative. The researcher problematizes the perception of time and the horizon, compares different timing of the past for himself and his interlocutor, and teases out caesurae in the structuring of time. In the last and partly self-ethnographic chapter on the ambivalence of fieldwork, the writer focuses on stories of "capturing" the reality, and stories about changing the approach to fieldwork and about the changed configurations of relations among actors.